Sex Differentiation from Fingerprint Ridge Density - Kandel, Jwala; Ghimire, Samjhana; Bhandari, Rashmita (Journal of Nobel Medical College, 2023)
Background: Determination of sex is an important parameter other than age, race and stature during forensic identification and crime scene investigation. Females tend to have finer and denser ridges on their fingertips than males. Present study aims at differentiating gender from fingerprint ridge density. Material and Methods: This is a cross sectional study conducted from March 2022 to March 2023 in Nobel Medical College Teaching Hospital, Nepal. Seven hundred fingerprints samples (350 males and 350 females), from 70 Nepalese medical students were collected and analyzed for gender differences. Comparative analysis was done using Student’s t-test (p<0.05). Likelihood ratio and posterior probability using Baye’s theorem were calculated to interpret the possibility of gender differentiation from various fingerprint ridge densities. Results: Students t-test revealed significant difference (p < 0.001) between the fingerprint ridge density of male and female (t= -16.733). The results showed ridge density <14/25mm2and >15/25mm2 are “more likely than not” from males and females respectively. Posterior probability using Baye’s theorem further revealed ridge density <13/25mm2 (C/C1=5.75,P=0.86) and >16/25mm2 (C1/C=4.29, P1=0.84) have higher probability of originating from males and females respectively. No any male and female had ridge density >16/25mm2 and <13/25mm2 respectively. Conclusion: The study revealsstatistically significantlygreater fingerprint ridge densities in female than in male Nepalese medical students.